GAMBARAN HASIL PEMERIKSAAN TUBERKULOSIS PARU DENGAN MENGGUNAKAN METODE TES CEPAT MOLEKULER (TCM) DI PUSKESMAS 7 ULU KOTA PALEMBANG TAHUN 2022 - M Nabil; Susni Sari; Rima Ernia; Rina SE Sitindaon (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Tuberculosis (TB) is still a public health problem and is the 13th leading cause of death in the world. TB is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Molecular Rapid Test (TCM) is one method that can be used to diagnose TB. This study aims to find out the description of the results of pulmonary TB examination using the Molecular Rapid Test Method (TCM) at the 7 Ulu Public Health Center, Palembang City in 2022. The results of the TCM examination obtained a total of 2635 patients with suspected pulmonary TB, of the number of patients negative results were more dominant compared to Rif Sen, Rif Res, and Rif Indet results. In patients with pulmonary TB based on male sex, the total was 272 patients and female sex as many as 187 patients. In this study, the male sex was more dominantly affected by pulmonary TB than the female sex. Meanwhile, in patients with pulmonary TB, the total productive age was 395 patients and 65 patients were not productive. In this study, productive age was more dominantly affected by pulmonary TB than non-productive age. The conclusion in this study is that male sex and productive age are more at risk of developing TB. Gender and age influence in this study. It is hoped that the community will prevent pulmonary TB by practicing a clean and healthy lifestyle, carrying out the BCG vaccination, and opening windows in the morning so that the house gets sunlight